Enhancing Data Provenance in mHealth: An Architecture Integrating FHIR with Blockchain - Velasco, Gislainy Crisostomo; Vaz, Noeli Antônia Pimentel; Vieira, Marcos Alves; Carvalho, Sergio T. (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2025)
The advancement of digitalization in healthcare, driven by mobile health (mHealth) applications, has expanded the collection and sharing of clinical data, making information traceability a significant challenge. Data provenance mechanisms are essential to record the origin, modifications, and access to information, thereby promoting transparency, trustworthiness, and security. Although models such as W3C PROV and FHIR Provenance exist, their adoption in mHealth remains limited, primarily due to the lack of compatible architectures and the scarcity of specific technical knowledge. This paper proposes a client-server architecture compatible with W3C PROV and FHIR Provenance, integrating a Provenance Gateway responsible for transforming clinical data into FHIR resources enriched with provenance information. Hyperledger Fabric also stores traceability metadata, ensuring immutability, integrity, and auditability without exposing sensitive data. Preliminary results indicate that the proposed approach enables integrating existing mHealth applications with data provenance mechanisms, promoting interoperability and control over information traceability.